Lymphocytic Hypophysitis Successfully Treated with Stereotactic Radiosurgery: Case Report and Review of the Literature - Pekic, Sandra; Bogosavljevic, Vojislav; Peker, Selcuk; Doknic, Mirjana; Miljic, Dragana; Stojanovic, Marko; Skender-Gazibara, Milica; Gacic, Emilija Manojlovic; Popovic, Vera; Petakov, Milan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Lymphocytic hypophysitis (LH) is an autoimmune inflammatory infiltration of the pituitary gland, usually with a benign evolution. In rare circumstances the inflammatory process may extend beyond the pituitary and infiltrate the surrounding structures. We present a 42-year-old woman affected by an aggressive form of LH with extension to the cavernous sinus causing internal carotid artery occlusion and right sixth cranial nerve palsy. Prednisone therapy caused severe iatrogenic Cushing's syndrome, and the patient underwent transsphenoidal decompression. The histopathology report was consistent with LH. The patient was symptom free for a short period with reappearance of severe headache, diplopia, and hearing loss (middle ear inflammation) 3 months after surgery. Corticosteroids were reintroduced with the addition of azathioprine, but there was no regression of the pituitary mass. The patient was referred for stereotactic radiosurgery (SRS) using Gamma Knife (15 Gy to the margin). After 26 months, azathioprine was stopped, and the dose of prednisone was gradually tapered to 7.5 mg/day. Sellar magnetic resonance imaging showed regression of the pituitary mass. After follow-up for > 3 years after SRS, there was no clinical or radiologic evidence of the disease, but carotid arteries remained occluded. The patient developed secondary hypothyroidism and hypogonadism as consequences of SRS. An aggressive form of LH extending beyond the pituitary gland infiltrating surrounding structures is described. It was successfully treated with SRS after failure of transsphenoidal surgery and combined immunosuppressive therapy (prednisone, azathioprine). The review of the literature presents timely information concerning treatment with azathioprine and SRS of patients with an aggressive form of LH.
Keywords: lymphocytic hypophysitis; prednisone; azathioprine; stereotactic radiosurgery